Enhancing insights: exploring the information content of calorespirometric ratio in dynamic soil microbial growth processes through calorimetry - Yang, Shiyue; Di Lodovico, Eliana; Rupp, Alina; Harms, Hauke; Fricke, Christian; Miltner, Anja; Kästner, Matthias; Maskow, Thomas (Frontiers in Microbiology, 2024)
Catalytic activity of microbial communities maintains the services and functions of soils. Microbial communities require energy and carbon for microbial growth, which they obtain by transforming organic matter (OM), oxidizing a fraction of it and transferring the electrons to various terminal acceptors. Quantifying the relations between matter and energy fluxes is possible when key parameters such as reaction enthalpy (∆rH), energy use efficiency (related to enthalpy) (EUE), carbon use efficiency (CUE), calorespirometric ratio (CR), carbon dioxide evolution rate (CER), and the apparent specific growth rate (𝜇𝜇 app ) are known. However, the determination of these parameters suffers from unsatisfying accuracy at the technical (sample size, instrument sensitivity), experimental (sample aeration) and data processing levels thus affecting the precise quantification of relationships between carbon and energy fluxes.To address these questions under controlled conditions, we analyzed microbial turnover processes in a model soil amended using a readily metabolizable substrate (glucose) and three commercial isothermal microcalorimeters (MC-Cal/100P, TAM Air and TAM III) with different sample sizes meaning varying volume-related thermal detection limits (LODv) (0.05-1 mW L -1 ). We conducted aeration experiments (aerated and un-aerated calorimetric ampoules) to investigate the influence of oxygen limitation and thermal perturbation on the measurement signal. We monitored the CER by measuring the additional heat caused by CO2 absorption using a NaOH solution acting as a CO2 trap. The range of errors associated with the calorimetrically derived 𝜇𝜇 app , EUE, and CR was determined and compared with the requirements for quantifying CUE and the degree of anaerobicity (𝜂𝜂 A ).Calorimetrically derived 𝜇𝜇 app and EUE were independent of the instrument used. However, instruments with a low LODv yielded the most accurate results. Opening and closing the ampoules for oxygen and CO2 exchange did not significantly affect metabolic heats. However, regular opening This is a provisional file, not the final typeset article during calorimetrically derived CER measurements caused significant measuring errors due to strong thermal perturbation of the measurement signal. Comparisons between experimentally determined CR, CUE, 𝜂𝜂 A , and modelling indicate that the evaluation of CR should be performed with caution.